DNA metabarcoding reveals microbial community dynamics in a microalgae-based municipal wastewater treatment open photobioreactor - Ferro, Lorenza; Hu, Yue O.O.; Gentili, Francesco G.; Andersson, Anders F.; Funk, Christiane (Algal research (Amsterdam), 2020)
Controlling the growth of desired algal strains in microalgal-based wastewater treatment systems is challenging, and understanding the dynamics and interactions in the system is vital for proper management. A pilot-scale open photobioreactor located in Northern Sweden, was inoculated with the culture collection strain Scenedesmus dimorphus UTEX 417, which had been grown in Nordic climate for 8 years. The microbial diversity of eukaryotic and prokaryotic communities and their seasonal dynamics were revealed throughout the growth period by high-throughput sequencing of 18S and 16S rRNA genes and correlated with various environmental factors. S. dimorphus was stable in batch culture, but other microalgae appeared during semi-batch mode and co-dominated the system as a consequence of predation by zooplankton. Desmodesmus, Pseudocharaciopsis, Chlorella, Characium and Oocystis were the main microalgal species co-occurring in the system, with Characium and Chlorella acting as main competitors to Scenedesmus. Proteobacteria, Firmicutes, Bacteroidetes and Actinobacteria were the most abundant bacterial phyla, some of which showing significant positive or negative influence on Scenedesmus growth over time. Light, temperature, dissolved oxygen, pH and nutrients concentrations were found to have significant influence on the bacterial and/or zooplanktonic community changes. [Display omitted] •Variation of microbial populations were studied in a North-Swedish photobioreactor.•Metabarcoding of 16S and 18S rRNAs revealed eukaryotic and prokaryotic communities.•The composition of zooplankton and bacterial communities followed seasonal variation.•Diversity of phytoplankton was altered by appearance and predation of zooplankton.•Native Nordic algae outcompeted the culture collection strain S. dimorphus UTEX 417.